Preserving genes, species, or ecosystems? Healing the fractured foundations of conservation policy - Bowen, Brian W. (Molecular ecology, 1999)
The scientific foundations of conservation policy are the subject of a recent tripolar debate, with systematists arguing for the primacy of phylogenetic rankings, ecologists arguing for protection at the level of populations or ecosystems, and evolutionary biologists urging more attention for the factors that enhance adaptation and biodiversity. In the field of conservation genetics, this controversy is manifested in the diverse viewpoints of molecular systematists, population biologists, and evolutionary (and quantitative) geneticists. A resolution of these viewpoints is proposed here, based on the premise that preserving particular objects (genes, species, or ecosystems) is not the ultimate goal of conservation. In order to be successful, conservation efforts must preserve the processes of life. This task requires the identification and protection of diverse branches in the tree of life (phylogenetics), the maintenance of life‐support systems for organisms (ecology), and the continued adaptation of organisms to changing environments (evolution). None of these objectives alone is sufficient to preserve the threads of life across time. Under this temporal perspective, molecular genetic technologies have applications in all three conservation agendas; DNA sequence comparisons serve the phylogenetic goals, population genetic markers serve the ecological goals, quantitative genetics and genome explorations serve the evolutionary goals.